Sinomenium acutum Modulates Platelet Aggregation and Thrombus Formation by Regulating the Glycoprotein VI-Mediated Signalosome in Mice - Yeon-Ji Kim; Tae In Kim; Ami Lee; Kyungho Kim; Youn-Hwan Hwang (MDPI AG, 2023)
Sinomenium acutum (SA) has long been used as a traditional medicine in China, Japan, and Korea to treat a wide range of diseases. It has been traditionally used to ameliorate inflammation and improve blood circulation. However, its role in platelet activation has not been thoroughly investigated. Hence, we conducted this study to assess the potential inhibitory effect of SA on platelet aggregation and thrombus formation. The antiplatelet activities of SA were evaluated by assessing platelet aggregation, granular secretion, intracellular Ca2+ mobilization, and the Glycoprotein (GP) VI-mediated signalosome. The thrombosis and bleeding time assays were used to investigate the effect of SA (orally administered at 50 and 100 mg/kg for seven days) in mice. SA treatment at concentrations of 50, 100, and 200 μg/mL significantly reduced GPVI-mediated platelet aggregation, granular secretion, and intracellular Ca2+ mobilization. Further biochemical studies revealed that SA inhibited spleen tyrosine kinase, phospholipase Cγ2, phosphatidylinositol 3-kinase, and AKT phosphorylation. Interestingly, oral administration of SA efficiently ameliorated FeCl3-induced arterial thrombus formation without prolonging the tail bleeding time. These findings suggest that SA has beneficial effects in thrombosis and hemostasis. Therefore, SA holds promise as an effective therapeutic agent for the treatment of thrombotic diseases.